What is Six-Questions Cognitive Model? - Tommy Tanu Wijaya (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2022)
Knowledge transfer is not easy especially for mathematics. Various factors need to be considered and think about how to transfer the knowledge effectively. The traditional teaching method does not help students to achieve deep learning and to solve this problem, there is a need to new learning method. The 6-questions cognitive model is a new learning model that is developed in China in 2012. This model can stand on its own or be combined with technology-based learning media. This research aims to introduce the 6-questions cognitive model by using a qualitative method. Researchers did literature research to know the deeper meaning of the 6-questions cognitive model. The result of this research shows that the cognitive model can help students to achieve deep learning and it can also be combined with a technology-based learning media. Teachers can use this research result to teach mathematics in school. Future research can find out about the effect of 6-questions cognitive model on the students' high order thinking skill.